SWEAR WORDS AND THEIR IMPLICATIONS FOR ENGLISH LANGUAGE LEARNING-TEACHING - Andang, Kristina; Bram, Barli (LLT Journal: A Journal on Language and Language Teaching, 2018)
This study attempts to explore the frequency of use of swear words and their implication for English language learning-teaching. Swear words or expletives are usually considered negative or rude to be used even in the United States or United Kingdom as English-speaking countries. In English language learning-teaching, swear words become part of linguistic studies and socio-cultural knowledge for teachers and students. This study aims to resolve two questions, namely first, what swear words have the highest frequency based on COCA and second, what implications of the frequency of swear words are for learners and teachers of English. Data were collected from a survey conducted using Facebook, which is a social medium used widely in both the United States and Indonesia for more than 13 years, and were retrieved from the Corpus of Contemporary American English (COCA), more precisely the frequency of swear words. The results of this study are expected to give knowledge on English language learning-teaching in a cultural context.